2006
DOI: 10.1371/journal.pmed.0030301
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obstructive Sleep Apnea Associates with Neuropsychological Deficits and Neuronal Brain Injury

Abstract: BackgroundChildhood obstructive sleep apnea (OSA) is associated with neuropsychological deficits of memory, learning, and executive function. There is no evidence of neuronal brain injury in children with OSA. We hypothesized that childhood OSA is associated with neuropsychological performance dysfunction, and with neuronal metabolite alterations in the brain, indicative of neuronal injury in areas corresponding to neuropsychological function.Methods and FindingsWe conducted a cross-sectional study of 31 child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
201
1
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(224 citation statements)
references
References 78 publications
(99 reference statements)
7
201
1
10
Order By: Relevance
“…[22][23][24][25][26][27][28][29][30] The plausibility of the obstructive sleep apnea syndrome contributing to cognitive deficits is supported by research showing impaired learning in juvenile rats exposed to intermittent hypoxemia 3 and by imaging studies showing cerebral neuronal injury in children with the syndrome. 30 Previous studies have shown differences in the cognitive function of children with the obstructive sleep apnea syndrome, as compared with controls. 19,27,31 However, baseline cognitive scores of children with the obstructive sleep apnea syndrome fell within the normal range, a finding similar to that in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26][27][28][29][30] The plausibility of the obstructive sleep apnea syndrome contributing to cognitive deficits is supported by research showing impaired learning in juvenile rats exposed to intermittent hypoxemia 3 and by imaging studies showing cerebral neuronal injury in children with the syndrome. 30 Previous studies have shown differences in the cognitive function of children with the obstructive sleep apnea syndrome, as compared with controls. 19,27,31 However, baseline cognitive scores of children with the obstructive sleep apnea syndrome fell within the normal range, a finding similar to that in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…19,27,31 However, baseline cognitive scores of children with the obstructive sleep apnea syndrome fell within the normal range, a finding similar to that in the current study. Cognitive and behavioral abnormalities have been shown to be reduced after adenotonsillectomy in some, [24][25][26][27]29 but not all, 30 nonrandomized studies, with inconsistency in the reported effect after treatment. 25,29,32 Previous studies have been limited by small samples, lack of randomization or appropriate controls, heterogeneous study groups, and sole reliance on parent questionnaires rather than including neuropsychological testing.…”
Section: Discussionmentioning
confidence: 99%
“…(1) SDB has been linked to hypertension,(2) growth failure,(3) enuresis, (4,5) and impairment of cognition, attention, and executive functions. (6)(7)(8)(9)(10)(11)(12) Identification of children at high risk for SDB and its associated morbidities is particularly important given the growing body of evidence that treatment with adenotonsillectomy may improve quality of life and neurocognitive function. (5,(13)(14)(15)(16)(17) Preterm infants are especially vulnerable both to SDB and its sequelae.…”
mentioning
confidence: 99%
“…Similarly, a recent study has shown metabolic alterations at the level of the hippocampus and the frontal cortex in children suffering from OSA in association with neuropsychic deficits that suggest a possible neural lesion related to OSA 5 .…”
Section: -A Short State Of the Artmentioning
confidence: 82%
“…Accordingly, electromyography analyses show that chronic partial enervation of the palatopharyngeal muscle can occur during episodes of OSA 5,14 . In short, structural changes, side effects of the vibration trauma related to snoring, can affect every component of the pharyngeal complex, and contribute to collapse of this segment of the airways.…”
Section: -A Short State Of the Artmentioning
confidence: 99%